Power, agency, and the hybrid peace paradigm: A post-colonial analysis of the US-led invasion of Afghanistan - Dias, Marta Cristina Santos (2024)
Hybrid approaches to peace and statebuilding, combining both top-down and bottom-up, local and international approaches and methods, are often presented as an emancipatory alternative to more conventional approaches to conflict management and post-war reconstruction. Against that backdrop, this dissertation investigates the extent to which hybrid approaches, while being framed as a more inclusive, flexible, and sustainable approach to peace and statebuilding, often perpetuate neo-colonial logics and power structures. Using the US-led intervention in Afghanistan as a case study, it demonstrates how this discourse and its concomitant practices help to naturalise the dominance of Western ideologies and interests, therefore reducing the agency of local and indigenous actors and, in doing so, facilitating the reintegration of domestic tensions and social instability. The study begins by tracing the historical evolution of peacebuilding paradigms, demonstrating how each generation has been underpinned by Western assumptions and interests and, when translated into practice, has maintained neo-colonial dynamics and relations. Following from that, and focusing on the US-led intervention in Afghanistan (2001-2021), which evolved from a conventional to a hybrid peace and statebuilding initiative, this dissertation explores how, in that specific context, international actors dictated political and economic processes, often at the expense of local needs and legitimacy. The analysis reveals the inherent contradictions of hybrid peacebuilding, where the superficial inclusion of local elements masks deeper continuities in global hierarchies. The findings suggest that while hybrid approaches claim to foster local ownership, they often perpetuate neo-imperial discourses which prioritise the interests of powerful states.